COVID-19 and Stressful Adjustment to Work: A Long-Term Prospective Study About Homeworking for Bank Employees in Italy - Orfei, Maria Donata; Porcari, Desirée Estela; D’Arcangelo, Sonia; Maggi, Francesca; Russignaga, Dario; Lattanzi, Nicola; Malizia, Andrea Patricelli; Ricciardi, Emiliano (Frontiers in Psychology, 2022)
The Covid 19 evolution has forced the massive introduction of homeworking for most employees in the initial stages of the pandemic and then the return to work, mainly thanks to the vaccination campaign. These multiple abrupt adjustment demands in work may be a source of intense stress for office workers with consequences on wellbeing and quality of life. The present long-term prospective study aimed at investigating the effect of adaptation demands on a broad population of employees of a large Italian banking group in the job-related stress framework. We administered a web-based survey to 1264 participants in Reopening after the first lockdown, from June to October 2020, at 841 subjects in Second Wave, corresponding to the rise of contagions from November 2020 to January 2021, and to 491 individuals in Vaccination Round, which ranged from February to June 2021. We assessed workaholism by the Dutch Work Addiction Scale (DUWAS-10), work-family conflicting overlap by the Work and Family Conflict Scale (WAFCS), and concern for back to work (BW) and for homeworking (HW) by specific questions. Higher WAFCS scores characterized Reopening and Vaccination Round while Second Wave had the highest level of concern for HW. Women and younger individuals showed the highest Concern for BW, WAFCS, and DUWAS-10 scores regardless of the pandemic stage. Homeworking days per week were related to more heightened concern for BW lower Concern for HW, DUWAS, and WAFCS scores. The number of children was related to lower Concern for BW and higher WAFCS scores in Reopening and Second Wave. Our data showed that massive adjustment demands in work and family routine represented a significant source of stress for employees, regardless of the different pandemic stages. The highest level of fatigue emerged in women and younger subjects. These results shed light on the need for a road map to promote a gradual and structured adjustment for workers and encourage organizations to consider homeworking a valid stable alternative.